2020
DOI: 10.3390/ijerph17176118
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Nutrition-Related Policies and Commitments of Major Food Companies in Australia, 2018

Abstract: The food industry has an important role to play in efforts to improve population diets. This study aimed to benchmark the comprehensiveness, specificity and transparency of nutrition-related policies and commitments of major food companies in Australia. In 2018, we applied the Business Impact Assessment on Obesity and Population Level Nutrition (BIA-Obesity) tool and process to quantitatively assess company policies across six domains. Thirty-four companies operating in Australia were assessed, including the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 22 publications
(34 reference statements)
4
20
0
Order By: Relevance
“…At the point that we conducted this study, we found that the lowest average energy content of children's combination deals offered by Oporto was 2500 kJ. Previous research, conducted in 2018 (40) , found that Subway had a commitment to providing a healthier side and drink option as the default option in their children's combination deals. Our results indicated that they are adhering to this commitment, with all children's combination deals offered by Subway classified as 'amber' (when the default sides and drinks were selected).…”
Section: Discussionmentioning
confidence: 79%
“…At the point that we conducted this study, we found that the lowest average energy content of children's combination deals offered by Oporto was 2500 kJ. Previous research, conducted in 2018 (40) , found that Subway had a commitment to providing a healthier side and drink option as the default option in their children's combination deals. Our results indicated that they are adhering to this commitment, with all children's combination deals offered by Subway classified as 'amber' (when the default sides and drinks were selected).…”
Section: Discussionmentioning
confidence: 79%
“…The median overall BIA-Obesity score across food industries in Europe was lower than what was found in Australia and New Zealand (21% vs. 41% and 38%, respectively). Previous studies showed that scores typically increase for companies engaging with the BIA-Obesity [ 24 , 26 , 28 ]. As such the difference in scores is likely due to the European assessment being based on only publicly available data, whereas for Australia and New Zealand the assessment included internal policy information provided by companies [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that scores typically increase for companies engaging with the BIA-Obesity [ 24 , 26 , 28 ]. As such the difference in scores is likely due to the European assessment being based on only publicly available data, whereas for Australia and New Zealand the assessment included internal policy information provided by companies [ 26 , 28 ]. Regardless of the root of the lower BIA-Obesity score, the lack of comprehensiveness, specificity and transparency of the publicly available commitments is concerning in light of their influence on food environments [ 10 , 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These concerns include children’s exposures to unhealthy food marketing and their vulnerability to its power [ 11 , 15 , 88 ], as well as poor media literacy education to moderate consumption of advertised foods [ 89 ]. Furthermore, the majority of the prominent food companies in Malaysia had poorer food industry commitments and disclosures related to promotion practices, compared to other countries [ 90 , 91 ]. Such local evidence highlights the need to enact stricter and comprehensive regulatory food marketing policies as a priority.…”
Section: Discussionmentioning
confidence: 99%